Pengendalian Kualitas Dengan Metode Statistical Process Control (SPC) Pada Line Produksi Semi Solid - Parama Pandu Novaliansyah; Jessica Martharia Putri Silalahi; Tulus Sukreni (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
Quality control for rejected/defective products at PT. Paragon Technology and Innovation must be improved to maintain customer trust and satisfaction. PT. Paragon Technology and Innovation is a company operating in the cosmetics industry. One of the departments in the company, the semi-solid plant, faces challenges where there are a significant number of rejected/defective products, leading to a high reprocessing rate performed by employees to meet the company's specifications for net product weight. The research to be conducted will utilize the Statistical Process Control (SPC) method for quality control and process documentation. This will enable further improvement steps to be taken to maintain process quality. This research indicates significant improvements in quality control processes aimed at enhancing customer and consumer satisfaction while reducing lead time in the production process. This is demonstrated by a Cp value of 0.76 and a Cpk value of 0.55, which align with the company's specification standards.